Regulation of Intestinal Immune Responses through TLR Activation: Implications for Pro- and Prebiotics - De Kivit, Sander; Tobin, Mary C.; Forsyth, Christopher B.; Keshavarzian, Ali; Landay, Alan L. (Frontiers in Immunology, 2014)
The intestinal mucosa is constantly facing a high load of antigens including bacterial antigens derived from the microbiota and food. Despite this, the immune cells present in the gastrointestinal tract do not initiate a pro-inflammatory immune response. Toll-like receptors (TLRs) are pattern recognition receptors expressed by various cells in the gastrointestinal tract, including intestinal epithelial cells (IEC) and resident immune cells in the lamina propria. Many diseases, including chronic intestinal inflammation (e.g. inflammatory bowel disease), irritable bowel syndrome (IBS), allergic gastroenteritis (e.g. eosinophilic gastroenteritis and allergic IBS) and infections are nowadays associated with a deregulated microbiota. The microbiota may directly interact with TLR. In addition, differences in intestinal TLR expression in health and disease may suggest that TLR play an essential role in disease pathogenesis and may be novel targets for therapy. TLR signaling in the gut is involved in either maintaining intestinal homeostasis or the induction of an inflammatory response. This mini review provides an overview of the current knowledge regarding the contribution of intestinal epithelial TLR signaling in both tolerance induction or promoting intestinal inflammation, with a focus on food allergy. We will also highlight a potential role of the microbiota in regulating gut immune responses, especially through TLR activation.